Press Release by Medco E&P Malaka on Serambi Indonesia Online News Coverage - Mansur, Suraya; Harsono, Sari Anggaraini (Universitas Semarang, 2020)
The study aims to analyze the public relations work suitability of PT Medco E&P Malaka related to community empowerment and social responsibility on Education and Training of 40 Acehnese Children in PPSDM-Cepu. International Standard Ambulance given for Pidie Jaya and the support from Medco E&P Malaka in the event Sail Sabang 2018 conducted by the company and press-released by Serambi Indonesia online in 2018. A qualitative approach with a case study method was employed in this study. The results showed that the point of view of journalists/media is dissimilar from the point of view of a company in writing a text. When media tend to publish articles based on a press release distributed by a company, then the company s image and reputation will be affected and become positive.